A rare presentation of gastric gastro-intestinal stromal tumour managed by stomach preserving surgery: a case report - Patil, Arun S.; Raut, Dnyaneshwar; Swami, Aishwarya V.; Hussain, Khadeija A.; Patil, Kanishk N. (International Surgery Journal, 2021)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the alimentary canal that account for 0.1–3% of all gastrointestinal malignancies. Vast majority of these tumors have oncogenic gain-of-function mutations of the KIT receptor tyrosine kinase. The mainstay of treatment is complete surgical resection followed by adjuvant therapy with tyrosine kinase inhibitors (Imatinib). We present a case report of 47 years old male presenting with a large abdominal lump, later diagnosed as a Gastrointestinal stromal tumor and underwent stomach preserving sleeve gastrectomy.